Smooth muscle tumor associated with Epstein Barr-virus in pediatric patients - Juliana Antinarelli Norberto da Silva; Patricio Cieri; Alexandre Alberto Barros Duarte; Fernanda Kelly Marques de Souza; Eliana Maria Monteiro Caran; Maria Teresa Alves de Seixas; Paola de La Iglesia Niveyro; Paula A. Coccia; Pablo Lobos; Simone de Campos Vieira Abib (Elsevier, 2023)
Epstein-Barr virus (EBV) is asymptomatic in most cases, however, the virus can be linked to pre-malignant lymphoproliferative diseases and to distinct human tumors. They can be classified as leiomyomas or leiomyosarcomas. Diagnosis depends on histopathology and EBV detection. Symptoms are associated with the lesion site. Various treatment modalities are described. It is mainly based on surgical resection, when possible, associated with reduced immunosuppression. It is also associated with targeted therapy and antiviral drugs. The role of surgery and chemotherapy are not well defined yet.A retrospective analysis of patients treated with this diagnosis was carried out at the Pediatric Oncology Institute - GRAACC/UNIFESP - Brazil and Hospital Italiano de Buenos Aires - Argentina, in the period from 2000 to 2020. Three medical records were found and the cases are described. All patients were immunocompromised. Two underwent resection of the tumoral lesion and one only clinical treatment and follow-up because tumors were considered unresectable. Long-term follow-up shows the importance of surgical resection. Surgery has a role in diagnosis too.This tumor is rare, especially in pediatric patients. Although surgical resection has impact in the long-term follow up, surgical treatment should be tailored depending on tumor resectability for each patient.